Phylogenetic implication of molecular genotyping of Euryops jaberiana Abedin & Chaudhary (Asteraceae) (Bangladesh Journal of Plant Taxonomy, 2016)
The taxonomic status of Euryops jaberiana Abedin & Chaudhary (tribe Senecioneae, family Asteraceae), endemic to northern Saudi Arabia was evaluated based on molecular phylogenetic analyses of internal transcribed spacer sequence (ITS) of nuclear ribosomal DNA (nrDNA) in order to ascertain its position within the genus. The phylogenetic tree constructed by the Neighbour Joining, Maximum Parsimony and Maximum Likelihood analyses showed a clear resolution of taxon included in the analyses at the level of sections, and E. jaberiana nested within the clade of the section Angustifoliae. E. jaberiana showed proximity with the allied species E. arabicus; however, a total number of eight nucleotide differences were evident between E. jaberiana and E. arabicus, indicating E. jaberiana as distinct from its allied species.Bangladesh J. Plant Taxon. 23(1): 45-51, 2016 (June)